Python-based PCA for Analyzing Financial Performance Changes in the Health Sector's Pharmaceutical Sub-Industry - Mulyo, Iksan Adityo; Heikal, Jerry; Gunawan , William Ben (Journal of Ecohumanism, 2025)
A meticulous examination of the financial status of 11 prominent pharmaceutical corporations was initiated through a comprehensive analytical investigation. Employing 15 pertinent financial metrics, encompassing indicators like the Price-Earnings Ratio (PER) and Net Profit Margin (NPM), allows for a thorough assessment of their financial health. The chosen analytical methodology is the Principal Component Analysis (PCA) technique. Over consecutive years, the analysis reveals that five companies—namely DVLA, KLBF, MERK, PEHA, and SOHO—demonstrate consistent performance by exhibiting minimal changes in their operational status. Firms categorized as "moderate" were questioned regarding potential limitations within their existing operational growth model or external hindrances impacting their advancement. Conversely, four companies—KAEF, PYFA, SIDO, and TSPC—exhibit positive trends and amplified performance. Notably, PYFA transitions from the "very poor" category to "fair" within a year, signifying potential strategic adaptations, effective crisis management, or advantageous market circumstances. Further investigation is warranted to delve deeper into directional shifts in strategies for change and distinctive approaches to fostering growth. In stark contrast, SCPI undergoes a significant downturn, marked by a "very poor" performance rating. These significant changes significantly differ from the overall organizational performance trend, indicating possible severe internal challenges or external pressures. This research fundamentally emphasizes the various changes in organizational performance within a single year, showcasing successful and stable organizations alongside those facing declines. Moreover, the findings underscore the imperative for continual self-assessment by organizations and the necessity to adapt strategies in response to internal and external environmental dynamics. This analysis serves as an initial step towards investigating causal factors impacting organizational performance, thereby facilitating the formulation of strategies geared towards future enhancement.